Smokers' risk perceptions and misperceptions of cigarettes, e‐cigarettes and nicotine replacement therapies. (19th June 2018) - King, Bill; Ndoen, Enjelita; Borland, Ron
Abstract: Introduction and Aims: To identify the range and coherence of smokers and recent ex‐smokers' general beliefs about the harms associated with smoking and the implications of these beliefs for their assessments of the relative harms and addictiveness of various nicotine containing products. Design and Methods: The study consisted of 18 single participant interviews with current smokers or vapers (13 M, 5 F) and three focus groups (15 M, 14 F) with current smokers/vapers and recent quitters. Both individual interviews and focus groups included semi‐structured discussions of how nicotine and cigarette smoke cause disease and addiction, and a structured task involving rating the relative harmfulness and addictiveness of 17 nicotine products against a reference, popular, cigarette. Results: Most participants were able to give adequate accounts of what makes cigarette smoking harmful and addictive but this general knowledge was not consistently applied to making harmfulness and addictiveness judgements about specific products. Many participants applied simple affect‐based heuristics to harmfulness and addictiveness judgments, even when they had apparently demonstrated more sophisticated knowledge earlier. Most used binary safe/dangerous thinking, with addictiveness and harmfulness strongly linked and a decoupling of satisfaction and addictiveness. Discussion and Conclusions: Many smokers appear to have reasonable general knowledge of the risks of smoking but cannot reliably apply this knowledge to practical risk judgements. We need to rethink how we communicate with the public about the risks of smoking, and using other nicotine products, in ways that allow them to make more informed decisions about their smoking.